Digestate Application on Grassland: Effects of Application Method and Rate on GHG Emissions and Forage Performance - Petr Šařec; Václav Novák; Oldřich Látal; Martin Dědina; Jaroslav Korba (Agronomy)
The application of digestate as a fertilizer offers a promising alternative to synthetic inputs on permanent grasslands, with benefits for productivity and environmental performance. This four-year study evaluated the impact of two digestate application methods—disc injection (I) and band spreading (S)—combined with four dose variants (0, 20, 40, and 80 m3·ha−1), including split-dose strategies. Emissions of ammonia (NH3), carbon dioxide (CO2), and methane (CH4) were measured using wind tunnel systems immediately after application. Vegetation status was assessed via Sentinel-2-derived Normalized Difference Vegetation Index, Normalized Difference Water Index, and Modified Soil Adjusted Vegetation Index, and agronomic performance through dry matter yield (DMY), net energy for lactation (NEL), and relative feed value (RFV). NH3 and CO2 emissions increased proportionally with digestate dose, while CH4 responses suggested a threshold effect, but considering solely the disc injection, CH4 flux did not increase markedly with higher application rates. Disc injection resulted in significantly lower emissions of the monitored fluxes than band spreading. The split-dose I_40+40 variant achieved the highest DMY (3.57 t·ha−1) and improved forage quality, as indicated by higher NEL values. The control variant (C, no fertilization) had the lowest yield and NEL. These results confirm that subsurface digestate incorporation in split doses can reduce emissions while supporting yield and forage quality. Based on the findings, disc injection at 40+40 m3·ha−1 is recommended as an effective option for reducing emissions and maintaining productivity in managed grasslands.